The Flowers in The Muses Garland. (8th September 2021) - Blayney, Peter W M
Abstract: A recent publication has laid the groundwork for future studies of printers' flowers. This paper begins by using the evidence of flowers to show that two seemingly unrelated printed fragments in the Beinecke Library come from a single book. An attempt to identify the printer then reveals the largely unexplored extent to which London printers' ornaments migrated to Scotland in the 1590s and came back in 1603, and that leads in turn to some new biographical facts about the printer Robert Waldegrave. An appendix looks at some later copies of Robert Granjon's best-known six-part combinable flower, which have too often been mistaken for the originals.